Implementasi Metode At-Taisir dalam Pembelajaran Tahfizh di Pondok Pesantren Mu’allimin Muhammadiyah Taajul Huffazh Pakan Sinayan - Rizki Wahyudi; Muhiddinur Kamal (Jurnal Cakrawala Akademika, 2024)
A unique educational approach is carried out at the Mu'allimin Muhammadiyah Taajul Huffazh Pakan Sinayan Islamic Boarding School, one of which is the Taisir teaching method. The teaching approach known as the "At-Taisir Method" focuses on understanding and adhering to the interpretation of the Koran. This research aims to provide evidence of the effectiveness of the At-Taisir method at the Mu'allimin Muhammadiyah Taajul Huffazh Pakan Sinayan Islamic Boarding School. The research method used is qualitative with a descriptive approach. Information regarding the application of the At-Taisir method in Islamic boarding schools was obtained through observation, interviews, and related documentation. Data were analyzed using qualitative descriptive techniques to understand the At-Taisir method testing. The application of the Taisir method in translating the Al-Qur'an at the Taajul Huffazh Pakan Sinayan Muhammadiyah Islamic Boarding School was successful, according to the research results. The At-Taisir method, which has been used at the Mu'allimin Muhammadiyah Taajul Huffazh Pakan Sinayan Islamic Boarding School, is an effective alternative for passing on Islamic teachings to future generations, especially the younger generation. The following are several application factors and methods used in the At-Taisir method at the Mu'allimin Muhammadiyah Taajul Huffazh Pakan Sinayan Islamic Boarding School: 1. It seems that some students are not yet able to read or understand the Al-Qur'an. 2. The teacher agrees upon learning activities. 3. As a source that invites students to study the Koran. 4. Hopefully, students will feel lazy about memorizing the Koran. 5. Students are variations of intelligence. 6. Time Allocation.